Prediction of dual survival following fetoscopic laser photocoagulation for twin–twin transfusion syndrome. (3rd April 2023) - Krispin, E.; Mustafa, H. J.; Espinoza, J.; Nassr, A. A.; Sanz Cortes, M.; Donepudi, R.; Harman, C.; Mostafaei, S.; Turan, O.; Belfort, M. A.; Shamshirsaz, A. A.
ABSTRACT: Objective: To develop a model based on factors available at the time of diagnosis of twin–twin transfusion syndrome (TTTS) for predicting the probability of dual twin survival following fetoscopic laser photocoagulation (FLP) using a machine‐learning algorithm. Methods: This was a retrospective study of data collected at two university‐affiliated tertiary fetal centers between 2012 and 2021. The cohort included monochorionic diamniotic twin pregnancies complicated by TTTS that underwent FLP. Data were stratified based on survival 30 days after delivery, and cases with dual survival were compared to those without dual survival. A random forest machine‐learning algorithm was used to construct a prediction model, and the relative importance value was calculated for each parameter that presented a statistically significant difference between the two study groups and was included in the model. The holdout method was applied to check overfitting of the random forest algorithm. A prediction model for dual twin survival 30 days after delivery was presented based on the test set. Results: The study included 537 women with monochorionic diamniotic twin pregnancy, of whom 346 (64.4%) had dual twin survival at 30 days after delivery and were compared with 191 (35.6%) cases that had one or no survivors. Univariate analysis demonstrated no differences in demographic parameters between the groups. At the time of diagnosis, the dual‐survival group had lower rates of estimated fetal weight (EFW) < 10 th centile for gestational age in the donor twin (56.4% vs 69.4%; P  = 0.004), intertwin EFW discordance > 25% (40.8% vs 56.5%; P  = 0.001) and anterior placenta (40.5% vs 50.0%; P  = 0.034). Comparison of Doppler findings between the two groups demonstrated significant differences in the donor twin, with a lower rate of pulsatility index (PI) > 95 th centile in the umbilical artery and ductus venosus and a lower rate of PI < 5 th centile in the fetal middle cerebral artery in the dual‐survival group. Relative importance values for each of these six parameters were calculated, allowing the construction of a prediction model with an area under the receiver‐operating‐characteristics curve of 0.916 (95% CI, 0.887–0.946). Conclusions: We developed a predictive model for dual survival in monochorionic twin pregnancies following FLP for TTTS, which incorporates six variables obtained at the time of diagnosis of TTTS, including donor EFW < 10 th centile, intertwin EFW discordance > 25%, anterior placenta and abnormal PI in the umbilical artery, ductus venosus and middle cerebral artery of the donor twin. This clinically applicable tool may improve treatment planning and patient counseling. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.